An international round robin test on isothermal (conduction) calorimetry for measurement of three-day heat of hydration of cement. (January 2016) - Wadsö, Lars; Arndt, Markus
Abstract: The results of a round robin test on isothermal (heat conduction) calorimetry are presented. A total of 18 participants using three types of instruments conducted 3-day measurements of the hydration of one rapidly hardening Portland cement and one slag-containing cement. The results confirm that isothermal calorimetry is a suitable method for the determination of heat of hydration. As a part of the study, two laboratories also conducted measurements with the standardized heat of solution method. For the Portland cement, these results were in good agreement with the isothermal measurements, but for the slag-containing cement the results differed, both between the two laboratories and between their results and the result of isothermal calorimetry. However, this method performance study clearly shows that the heat of hydration determination of cement by heat conduction calorimetry is more precise than the traditional heat of solution method described in EN 196-8, if state-of-the-art calorimeters are used.